2020
DOI: 10.1155/2020/6974050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Implant Thread Morphology on Primary Stability: A Prospective Clinical Study

Abstract: Objectives. The purpose of this study was to evaluate the primary stability of two implants with the same macro- and micromorphology but different thread design and analyze their clinical outcomes over a one-year period. Materials and Methods. 14 patients needing a partial rehabilitation with a delayed loading approach (DEL group: 9 patients) or a full-arch rehabilitation treated with immediately loaded fixed prostheses supported by 4 implants following the Columbus Bridge Protocol (CBP) (IL group: 5 patients)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…Implant A showed double threads for increasing the contact area with the bone and reducing the cortical occlusal stress. This macro-morphology appeared to be more favorable in terms of surface changes during the implant placement than the single-threaded ones, even if it was able to ensure a faster implant insertion [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Implant A showed double threads for increasing the contact area with the bone and reducing the cortical occlusal stress. This macro-morphology appeared to be more favorable in terms of surface changes during the implant placement than the single-threaded ones, even if it was able to ensure a faster implant insertion [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that not only the depth but also the shape of the screw threads can influence the primary stability of a dental implant and the peri-implant bone resorption. Thus, it has been shown that occlusal loads after implant placement are mainly concentrated in the bone section adjacent to the first screw winding, indicating that the implant width and the configuration of the windings could lead to a reduction of the loads [ 14 , 15 , 20 ]. For example, a more square shape of the threads allowed an increase of the bone–implant contact as well as a distribution of the loads on a larger bone surface with a better distribution, especially of lateral forces.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a more square shape of the threads allowed an increase of the bone–implant contact as well as a distribution of the loads on a larger bone surface with a better distribution, especially of lateral forces. A V-shape of the threads in the most apical part of the implant determines a greater aggressiveness of the implant, especially in bone of lower density, achieving a greater mechanical stability of the implant and a greater resistance to vertical forces [ 14 , 20 , 46 ]. Not only do the observed effects of apically located screw threads on the primary stability of the implant correspond to the current literature, but also fit the mathematical calculations for improving the pressure distribution around the implant by increasing the surface area [ 14 , 16 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deeper threads can provide an additional advantage in the tapered fixture design since the engagement of more threads in the bone may provide greater stability when there is lack of bone or the quality of bone is poor (Lee et al, 2015), such as for an extraction socket during immediate implant placement. However, the larger discrepancy between the drill and fixture diameters associated with deeper threads may negatively affect the placement accuracy, especially in the presence of a peri‐implant dehiscence or at an extraction socket (Menini et al, 2020). However, no previous study has verified this hypothesis.…”
Section: Introductionmentioning
confidence: 99%